A Newly Recorded Mite Species from Turkey: Eupalopsellus deformatus Fan (Acari: Eupalopsellidae) - Doğan, Sibel; Doğan, Salih; Erman, Orhan; Sevsay, Sevgi; Adil, Sezai (Fırat University, 2017)
Eupalopsellus deformatus Fan was herein described and figured based on specimen collected from moss and lichen in Örümcek Forests (Turkey). This species is a new record for the mite fauna of Turkey

Eupalopsellus deformatus Fan Örümcek Ormanları’ndan (Türkiye) alınan yosun ve likenden toplanan örnek üzerinden tanımlandı ve şekilleri çizildi. Bu tür, Türkiye akar faunası için yeni kayıttır.
Türkiye’den Yeni Bir Akar Türü Kaydı: Eupalopsellus deformatus Fan (Acari: Eupalopsellidae)